SEPARATE AND COMBINED EFFECTS OF MACROPHOMINA PHASEOLINA AND COPPER ON GROWTH, PHYSIOLOGY AND ANTIOXIDATIVE ENZYMES IN VIGNA MUNGO L - S. Akhtar; A. Shoaib; N. Akhtar; R. Mehmood (Journal of Animal and Plant Sciences, 2016)
Food poisoning due to toxicity of heavy metals and pathogenic microorganisms is a major food safety issue that impacts on agriculture production. In the current research work, polygonal interaction of plant-pathogen-metal was investigated in vitro in terms of seed germination, seedling growth, physiology and antioxidant enzymes activity in Vigna mungo L. An experiment was conducted in growth chamber in glass Petri plates contained mash bean seeds on sterilized filter papers provided with spore suspension of M. phaseolina and four different concentrations of copper [Cu(II)] (25, 50, 75 and 100 ppm) either alone and in combination. Germination and seedling growth were significantly decreased by 40-98% and 30-98% due to separate effect of M. phaseolina and Cu, respectively. Germination and seedling growth were either insignificantly affected or stimulated at lower concentration (25 ppm) of Cu, while declined by 10-62% with increase in metal concentration from 50-100 ppm given in combination with pathogen. Total chlorophyll, sugar and carotenoid contents were reduced, while proline and total phenolic contents were increased due to given stresses. However, both proline and total phenolic contents were gradually decreased with increasing amount of Cu treatment (25-100 ppm). Antioxidant enzymes activities (peroxidase, polyphenol oxidase, catalase and superoxide dismutase) were increased to variable extents in all treatments. It was concluded that detrimental effect of Cu was increased with increase in its concentration. The simultaneous occurrence of M. phaseolina and excess Cu decreased harmful effect of individual stress on the plant.
Keywords: Copper; charcoal rot; M. phaseolina; toxicity; legumes; black gram